PENGARUH PEMANFAATAN CHATGPT TERHADAP MINAT BELAJAR SISWA DALAM KONTEKS TEKNOLOGI PENDIDIKAN : STUDI LITERATUR - Mutiara Putri Chandra; Firman; Netrawati (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Advances in digital technology have transformed various aspects of life, including the world of education. One rapidly developing innovation is ChatGPT, an artificial intelligence-based application capable of providing interactive answers to user questions. This article aims to analyse how the use of ChatGPT can influence student learning interest in the context of educational technology use. This study examines three main variables: ChatGPT as a digital learning medium, students' learning interest, and the integration of technology in learning. Using a descriptive qualitative approach, this article presents a literature review and previous research findings that support the importance of technology adaptation in enhancing student engagement.